2016
DOI: 10.1017/ipo.2016.13
|View full text |Cite
|
Sign up to set email alerts
|

Contexts, networks, and voting behavior: the social flow of political communication in Italy

Abstract: Previous research demonstrated that different contextual sources can affect voting behavior. Homogeneous familiar networks affect individual behavior of people embedded in these networks toward voting for certain parties. Moreover, being exposed to higher levels of homogeneity in the geographical place where one lives contributes to developing higher propensities to vote for a certain political object. By means of 2006 National Italian Elections data (and by employing new measures of network political homogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In most of the data used to study political discussions and voting behavior, alter's characteristics are ego‐reported, for instance in ANES (Erisen & Erisen, ), GLES (Schmitt‐Beck, Bytzek, Rattinger, Roßteutscher, & Weßels, ), and ITANES (Mancosu, ; Vezzoni, ; Vezzoni & Mancosu, ). As pointed out by Huckfeldt and Sprague (), this design is suboptimal, as respondents' perceptions are potentially affected by cognitive biases that could undermine the validity of such information, especially when referring to alters' political attitudes.…”
mentioning
confidence: 99%
“…In most of the data used to study political discussions and voting behavior, alter's characteristics are ego‐reported, for instance in ANES (Erisen & Erisen, ), GLES (Schmitt‐Beck, Bytzek, Rattinger, Roßteutscher, & Weßels, ), and ITANES (Mancosu, ; Vezzoni, ; Vezzoni & Mancosu, ). As pointed out by Huckfeldt and Sprague (), this design is suboptimal, as respondents' perceptions are potentially affected by cognitive biases that could undermine the validity of such information, especially when referring to alters' political attitudes.…”
mentioning
confidence: 99%
“…First, because social networks are important providers of resources of all kind, they function as pool of information for the voters. In that perspective, citizens are influenced by the networks they form with people they closely interact, exchange, discuss, and disagree politics (Pattie and Johnston 2001;Huckfeldt et al 2004;Eveland and Hively 2009;Mancosu 2016;Butters and Hare 2020). The vote for populist parties in Italy has been consistently driven by informal share of information with close social network contacts (Vezzoni and Mancosu 2016).…”
Section: Social Network and The (Radical) Votementioning
confidence: 99%
“…In addition, there are good reasons to believe that the effect goes from interpersonal discussion to behaviour (and not the other way), due to the fact that choices of conversation partners are often constrained and many citizens find themselves confronted with views they do not share, even if they would prefer to avoid such views (Lazer et al, 2010). In the Italian context, there is evidence that political diversity is not rare and that Italian people often discuss politics with those who hold different views especially within weak ties (Campus et al, 2008;Baldassarri, 2009;Mancosu, 2016;Vezzoni and Mancosu, 2016).…”
Section: Designmentioning
confidence: 99%